Compliance with infection prevention and control practices and associated factors among healthcare workers in Tanzania: Experience from a secondary level-referral hospital - Cesilia Charles; Lutengano Mkonongo; David Masanja; Pendo Edward; Damian Maruba; Philipo Felix Mwita; Baraka Nkondo; Frank Elisha; Edward Bucheye; Abel Nyika; Avent Kalumiana; Emmanuel Amsi; et al. (PLoS ONE, 2026)
Introduction Compliance with Infection Prevention and Control practices remains a key challenge, affecting the safety of both patients and healthcare workers. Poor compliance raises the risk of Hospital-Acquired Infections (HAIs) and antimicrobial resistance (AMR). Objective This study aimed to assess compliance levels and factors associated with infection prevention and control practices among HCWs at Katavi Referral Regional Hospital (KRRH) in Tanzania. Methods A hospital-based cross-sectional study was conducted among 195 healthcare workers from July 24 to August 23, 2025. Questionnaires and observation checklists were used to collect sociodemographic data, compliance levels, individual-level factors, hospital-level factors, and the availability of IPC supplies. A validated Compliance with Standard Precautions Scale (CSPS) tool, developed by the WHO, was used to measure compliance levels. Data were analysed in STATA (version 15.0), using bivariate and multivariate modified Poisson regression models. Adjusted Prevalence Ratio (APR) with 95% Confidence Interval (CI) was used to assess factors associated with IPC compliance. Results The study revealed that the overall compliance with IPC practices among healthcare workers was 68.9%. Only 39.0% of HCWs demonstrated high overall compliance with IPC practices (<80%), while 61% had low overall compliance (>80%). Also, factors significantly associated with compliance with IPC practices were doctor profession (APR: 0.32;95% CI:0.19,0.57), blood/body fluid exposure (APR: 1.55;95% CI:1.095,2.19), motivation at workplace (APR: 1.43;95% CI:1.02,2.02), supportive supervision (APR: 1.92;95% CI:1.09,3.38), and presence of IPC committee (APR: 1.61;95% CI:1.07,2.40). The most common available IPC supplies were hand hygiene items, personal protective equipment, and waste management items (100%). However, some IPC supplies were unavailable, including water (44.4%) and soap (55.6%) in latrines. Conclusion Overall compliance with IPC practices among HCWs remained suboptimal. Improving compliance requires strengthening IPC governance through functional IPC committees, enhancing supportive supervision and motivation, and addressing persistent infrastructural and resource gaps within health facilities.